Assessing uncertainties in climate change impacts on runoff in Western Mediterranean basins - D. Ruelland; P. Hublart; Y. Tramblay (Proceedings of the International Association of Hydrological Sciences, 2015)
This paper investigates the uncertainties linked to climate change impacts on runoff in four mesoscale basins (900 to 1800 km2) in the Mediterranean region. Runoff simulations were based on a daily conceptual model including a snow module. The model was calibrated and validated according to a differential split-sample test over a 20-year period and four competing criterions aiming to represent model structural uncertainty based on the concept of Pareto optimality. Five regional climate models (RCMs) from the Med-CORDEX initiative were used to provide temperature and precipitation projections under RCP8.5 by 2050. The RCMs' inability to realistically simulate reference climate (notably precipitation) led us to apply a monthly perturbation method in order to produce a range of climate scenarios. The structural uncertainty bounds obtained from the hydrological simulations over the reference period showed that the model was able to correctly reproduce observed runoff despite contrasted hydrological conditions in (and in between) the basins. Climate projections were shown to be convergent regarding temperatures, which could increase by about +1 to 3 °C on each basin. In contrast, no clear trends in precipitation could be put in evidence, some RCMs leading to a mean annual precipitation decrease (up to 64%), and others to an increase (up to 33%). The hydrological projections resulted from the combination of the hydrological simulation bounds with the range of climate projections. Despite the propagation of those uncertainties, the 2050 hydrological scenarios agreed on a significant runoff decrease (2–77%) during spring on all basins. On the opposite, no clear trend in runoff could be observed for the other seasons.